2017
DOI: 10.1038/s41598-017-14808-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics induce polarization of pleural macrophages to M2-like phenotype in patients with tuberculous pleuritis

Abstract: Pleural macrophages play critical roles in pathogenesis of tuberculous pleuritis, but very little is known about their response to anti-tuberculosis antibiotics treatment. Here, we examined whether and how pleural macrophages change in phenotype, transcription and function following antibiotics treatment in patients with tuberculous pleuritis. Results show pro-inflammatory cytokines were down-regulated significantly post antibiotic treatment in the pleural effusions and pleural macrophages up-regulated markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…We observed a higher M2 macrophage polarization rate in TB patients treated with anti-TB drug regimens including pyrazinamide or a combination of pyrazinamide, prothionamide and cycloserine. Consistently, a previous report suggested that pyrazinamide treatment influences the host immune response [15,16,29]. These observations suggest that anti-TB drugs modulate the host immune response.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We observed a higher M2 macrophage polarization rate in TB patients treated with anti-TB drug regimens including pyrazinamide or a combination of pyrazinamide, prothionamide and cycloserine. Consistently, a previous report suggested that pyrazinamide treatment influences the host immune response [15,16,29]. These observations suggest that anti-TB drugs modulate the host immune response.…”
Section: Discussionsupporting
confidence: 87%
“…Especially in the case of TB, long-term medication with anti-TB drugs is necessary for successful treatment, and therefore, the effects of drug-mediated immunomodulation may be large. Some antimicrobial agents have immunomodulatory properties in vitro [12,28], and some anti-TB drugs induce M2-like polarization of pleural macrophages in patients with pleuritic TB [16]. We observed a higher M2 macrophage polarization rate in TB patients treated with anti-TB drug regimens including pyrazinamide or a combination of pyrazinamide, prothionamide and cycloserine.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Activation of M1 macrophages through the TLR2 signal pathway can be benefi cial for the host to inhibit growth and the survival of M. tuberculosis. 16,17 Increased activation of M1 macrophages in newly infected RR pulmonary TB will produce pro-infl ammatory cytokines which play a role in the mechanism of eliminating M. tuberculosis. This causes the level of pro-infl ammatory cytokines to be higher in RR pulmonary TB serum compared to RS pulmonary TB.…”
Section: Il-18 Levelmentioning
confidence: 99%
“…Initially, IL-10 is known to be secreted by antigen-stimulated Th2, but it is now known that IL-10 is not only secreted by Th2, but also secreted by a subset of CD4 + T cells, including Th1 and Th17, B cells, neutrophil cells, and macrophages. 17 IL-10 is generally thought to modulate the ability of the immune response and allow bacterial elimination without damaging the host tissue, but in some cases the absence of IL-10 makes the immune response more eff ective in eliminating pathogens, but resulting in more damage to the tissue and aff ects the survival of the host. 20,21 The mean level of IL-10 in pulmonary TB patients with RS and RR in this study were 128.81 ± 135.77 pg/ml and 125.15 ± 118.32 pg/ ml respectively.…”
Section: Il-10 Levelmentioning
confidence: 99%